The Impact of COVID-19 on the Stock Markets of BRICS Countries - Kok, Sook Ching; Caroline Geetha (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2023)
This paper examines the weak-form efficiency of the BRICS stock markets for the periods before and during the outbreak of the COVID-19 pandemic. The five countries of BRICS are Brazil, Russia, India, China, and South Africa. The performance of Brazil’s stock market is shown by the BOVESPA Index. The MOEX Russia Index is used to show the performance of Russia’s stock market. For India’s stock market, the S&P BSE SENSEX Index is used. For China, the stock market is represented by the SHCOMP Shanghai Stock Exchange Composite Index. South Africa Top 40 Index represents South Africa’s stock market. We use unit root tests to assess the random walk properties of the series. We found that Brazil’s stock market and China’s stock market were following a random walk or efficient for both the periods before and during the outbreak of the COVID-19 pandemic. For the period before the pandemic, Russia’s stock market and India’s stock market did not follow a random walk or were inefficient only when the trend was included in the testing of unit root. For the period during the outbreak of the pandemic, both the stock markets were following a random walk or became efficient. For the period before the pandemic, we also found that South Africa’s stock market was not following a random walk when only intercept is included in the testing of unit root. During the pandemic, South Africa’s stock market was following a random walk or became efficient. The interesting results showed that all the BRICS countries’ stock markets were or became efficient during the pandemic period. This may show that the market confidence was strong even though these countries, like other countries, were badly impacted by the pandemic catastrophe.